The critical role of education and ICT in promoting environmental sustainability in Eastern and Southern Africa: A panel VAR approach - Olatunji Abdul Shobande; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
The struggle to combat climate change remains complex and challenging. Currently, two climate change approaches, namely, mitigation and adaptation, have been widely supported. These are empirical, requiring further explanation of the main drivers of carbon emissions. This research seeks to tackle this problem by providing a strategy to reduce climate change impacts. This study contributes to the existing empirical literature in several ways. It investigates whether education and information and communication technology (ICT) matter to promote environmental sustainability in the Eastern and Southern Africa. The empirical evidence is based on the third-generation panel unit root test and panel cointegration tests that account for the potential issue of structural breaks in the series. We further dissect the long and short run dynamics using the panel Granger causality approach. Our findings show the possibility of using education and clean technology investment in a complementary strategy for mitigating carbon emissions and promoting environmental sustainability in the sampled countries.
Keywords: C52; O38; O40; O55; P37; 330; Environmental Sustainability; ICT; Education; Eastern Africa; Southern Africa